2020
DOI: 10.1371/journal.pone.0233125
|View full text |Cite
|
Sign up to set email alerts
|

Standardized on-road tests assessing fitness-to-drive in people with cognitive impairments: A systematic review

Abstract: The on-road assessment is the gold standard because of its ecological validity. Yet existing instruments are heterogeneous and little is known about their psychometric properties. This study identified existing on-road assessment instruments and extracted data on psychometric properties and usability in clinical settings. Method A systematic review identified studies evaluating standardized on-road evaluation instruments adapted for people with cognitive impairment. Published articles were searched on PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 74 publications
(128 reference statements)
0
10
0
Order By: Relevance
“…On-road testing is considered the “golden standard” in determining driving fitness. Yet, on-road evaluation reliability and validity are at times questionable, due to methodological and environmental influences ( 45 ). Finally, future studies should include more than a single on-road experience to increase the sensitivity to detecting changes in estimation and to obtain a broader understanding of driving self-awareness.…”
Section: Discussionmentioning
confidence: 99%
“…On-road testing is considered the “golden standard” in determining driving fitness. Yet, on-road evaluation reliability and validity are at times questionable, due to methodological and environmental influences ( 45 ). Finally, future studies should include more than a single on-road experience to increase the sensitivity to detecting changes in estimation and to obtain a broader understanding of driving self-awareness.…”
Section: Discussionmentioning
confidence: 99%
“…That said, systematic reviews on measurement properties of instruments other than patient-reported outcome have been conducted using the COSMIN guidelines. 59 , 60 , 61 Further amendments on the guidelines should be made for appraising TCM diagnostic instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the presented considerations, and to enhance the ecological validity of findings, the specific aim of this study was to compare real on-road driving performances in healthy and experienced older vs. younger drivers using an assessment form based on current driving-license examination guidelines in Norway and items from other tests designed for testing driving performance. Use of on-road tests and expert examiners to assess driving skills and driving performance are referred to as a "gold standard" assessment (Bellagamba et al, 2020). An on-road test conducted in real road and traffic environment are likely to give a more nuanced impression of driving skills and performance compared to only use of driving simulators, VR-glasses, or similar.…”
Section: The Present Studymentioning
confidence: 99%